Morphological traits and molecular analysis for two new Chrysosporium species from Fujian Province, China - Li, Zhong; Zhang, Yan-Wei; Chen, Wan-Hao; Han, Yan-Feng (Phytotaxa, 2019)
Two new species, Chrysosporium laterisporum and C. ovalisporum, were isolated from forest soils and zoo soils in Fuzhou City, Fujian Province, China, using child hair as baits. Molecular (ITS-5.8S rDNA sequences) and morphological characters were used to identify taxonomic status. The phylogeny showed C. laterisporum and C. ovalisporum grouped into a separate subclade, closely related to C. georgii, C. magnasporum, C. oceanitesii and C. vespertilium. These previously described Chrysosporium species can be distinguished from the new species based on morphology alone.